THE INFLUENCE OF A STRUCTURED INQUIRY LEARNING MODEL ON INCREASING SCIENCE LITERACY COMPETENCY IN CLASS VIII OF SMP NEGERI 01 BAJENG - Nurul Magfhira K.; Nurhayani H. Muhiddin; Ramlawati Ramlawati (Universitas Negeri Makassar, 2024)
This study aims to: 1) find improvement of science literacy of VIII grade students of SMP Negeri 01 Bajeng, Gowa Regency who were taught using structure inquiry learning model and who were taught using conventional learning model, 2) the effect of structured inquiry learning model on improving science literacy. The population of this study was all students of class VIII of SMP Negeri 01 Bajeng, Gowa, totaling 9 classes with a total of 309 students. Sampling was taken using a purposive sampling technique to obtain class VIIIA as an experimental class with a total of 29 students and VIIIB as a control class with a total of 29 students. The results showed that 1) the science literacy competency of students who were taught using a structured inquiry learning model on the material of “Light and Optical Devices” increased with an average N-gain score of 0.54 in the medium category. Students’ science literacy who are taught using conventional learning models has increased with an average N-gain score of 0.40 in the moderate category, 2) there is an effect of structure inquiry learning model on improving the science literacy competence of students in class VIII SMP Negeri 01 Bajeng